2014
DOI: 10.1002/jso.23651
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative neutrophil–lymphocyte ratio predicts recurrence and survival among patients undergoing R0 resections of adenocarcinomas of the esophagogastric junction

Abstract: The present study indicates that elevated preoperative NLR (≥ 5) is a useful marker of tumor recurrence and independently predicts poorer disease-free and overall survival among patients with AEG undergoing R0 resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 46 publications
(54 reference statements)
5
48
1
3
Order By: Relevance
“…The most common tumor site was the temporal lobe (37.2%), followed by the occipital lobe (27.5%). The mean tumor volume was 32.1 ± 27.3 cm 3 . In 19 cases (37.2%), the tumor was located close to a ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common tumor site was the temporal lobe (37.2%), followed by the occipital lobe (27.5%). The mean tumor volume was 32.1 ± 27.3 cm 3 . In 19 cases (37.2%), the tumor was located close to a ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] NLR is an inexpensive and widely available biomarker of glioblastoma aggressiveness, and thus should be used alongside current glioblastoma prognostic factors. Nevertheless, there is obviously a need for future studies with larger numbers of patients in order to confirm our preliminary observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some reports have been published to assess the prognostic role of NLR in the peripheral blood of patients with malignant diseases. An increased NLR is associated with poor, late prognosis of various malignancies, including pancreatic or oesophageal cancer [6,7]. Recently, NLR has also been evaluated as a predictor of major postoperative complications in abdominal surgery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative blood samples for neutrophil and lymphocyte counts are taken for almost all colorectal cancer patients, and the NLR can be simply calculated. It has been reported that NLR is a prognostic factor for various cancers, such as advanced cancer [9], pancreatic cancer [10], non-small cell lung cancer [11], cancer of esophagogastric junction [12], gastric cancer [13], lung cancer [14], and head and neck cancer [15]. Pre-treatment NLR has also been reported as a prognostic factor for colorectal cancer [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%